Evaluation of Three Formulations of Culture Media for Isolation of Brucella spp. regarding Their Ability to Inhibit the Growth of Contaminating Organisms - Vicente, Acacia F. [UNESP]; Antunes, Joao M. A. P. [UNESP]; Lara, Gustavo H. B. [UNESP]; Mioni, Mateus S. R. [UNESP]; Allendorf, Susan D. [UNESP]; Peres, Marina G. [UNESP]; Appolinario, Camila M. [UNESP]; Listoni, Fernando J. P. [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Megid, Jane [UNESP] (Hindawi Publishing Corporation, 2014)
Three culture media (Brucella agar, Farrell medium, and CITA) were compared for their effectiveness in inhibiting contamination and for isolating Brucella spp. One hundred lymph nodes from pigs (n = 50) and wild boars (n = 50) with lymphadenitis were collected in slaughterhouses in the State of Sao Paulo and were assessed on these three selective media for Brucella spp. All of the samples were negative for Brucella spp. on the three culture media. On the agar medium, fungal (70 plates) and Gram-positive bacterial (59 plates) contaminants were observed; in the CITA medium, the absence of fungal and Gram-positive bacteria on 15 plates was observed; no bacterial or fungal growth was observed on the Farrell media. The results demonstrated that the CITA and Farrell media inhibited the growth of contaminants better than the Brucella agar.